'I have only little English': language anxiety of Filipino migrants with chronic disease. Issue 6 (1st November 2016) - Maneze, Della; Everett, Bronwyn; Kirby, Sue; DiGiacomo, Michelle; Davidson, Patricia M.; Salamonson, Yenna
ABSTRACT: Objective: This study investigates communication challenges faced by Filipino patients with chronic diseases when engaging with healthcare professionals (HCPs). Design: Nine focus groups were conducted between November 2010 and June 2011. Results : Two main categories of themes were identified: patient-related and HCP-related factors. Patient-related factors included three subthemes: (1) lack of confidence in their English language abilities in clinical situations; (2) cultural attitudes; and (3) strategies used to improve communication. Older Filipinos with chronic disease were anxious about their lack of ability to explain their symptoms in English and were concerned that asking questions was conveying distrust in the HCPs. Most of the elderly simply nodded their head to indicate they understood even if they did not, for fear of being thought 'stupid'. Many participants preferred Filipino GPs or have a relative interpret for them. Two subthemes were related to HCPs including (1) not being listened to and (2) assumptions of understanding. HCPs were thought to assume English language skills in Filipino patients and therefore were not careful about ensuring understanding. Conclusions : These findings highlighted the need for HCPs to be more aware of 'grey areas' in English-language proficiency and the cultural lens through which migrants understand health.